2013
DOI: 10.1111/febs.12227
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate inhibits platelet‐derived growth factor‐induced proliferation and migration in pulmonary artery smooth muscle cells through Akt inhibition

Abstract: Sodium butyrate (BU) is a molecule that acts as a histone deacetylase inhibitor. As compared with its well-known antineoplastic/antiproliferative effects, little is known about BU action on vascular cell dynamics. An imbalance of proliferation and migration in pulmonary arterial smooth muscle cells (PASMCs) is essential in the onset and progression of pulmonary arterial hypertension (PAH), a disease that is characterized by vascular lung derangement and that frequently has an unfavorable outcome. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 36 publications
5
36
0
Order By: Relevance
“…Activation of G proteincoupled receptors (GPCRs) and RTKs by mitogenic and angiogenic factors, cytokines, and hormones is one of the important mechanisms leading to cell growth, proliferation, and migration. Upregulated expression and increased function of RTK ligands (e.g., PDGF and VEGF) (47) and RTKs (e.g., VEGFR and PDGFR␣/PDGFR␤) (7,21,31) in the pulmonary vascular cells (including fibroblasts, smooth muscle cells, and endothelial cells) are believed to play an important role in the initiation and progression of PA wall thickening, as well as the neointimal lesions and intraluminal obliteration observed in patients with PAH and animals with experimental pulmonary hypertension (4,36,46). Blockade of various RTKs and GPCRs in the plasma membrane of pulmonary vascular smooth muscle cells and endothelial cells using nonselective and selective receptor antagonists (e.g., imatinib) has been proven to have therapeutic effects on pulmonary hypertension (18,20,46,53,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of G proteincoupled receptors (GPCRs) and RTKs by mitogenic and angiogenic factors, cytokines, and hormones is one of the important mechanisms leading to cell growth, proliferation, and migration. Upregulated expression and increased function of RTK ligands (e.g., PDGF and VEGF) (47) and RTKs (e.g., VEGFR and PDGFR␣/PDGFR␤) (7,21,31) in the pulmonary vascular cells (including fibroblasts, smooth muscle cells, and endothelial cells) are believed to play an important role in the initiation and progression of PA wall thickening, as well as the neointimal lesions and intraluminal obliteration observed in patients with PAH and animals with experimental pulmonary hypertension (4,36,46). Blockade of various RTKs and GPCRs in the plasma membrane of pulmonary vascular smooth muscle cells and endothelial cells using nonselective and selective receptor antagonists (e.g., imatinib) has been proven to have therapeutic effects on pulmonary hypertension (18,20,46,53,56).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vascular remodeling or concentric vascular wall thickening of small pulmonary arteries (PAs) and arterioles, attributable partially to enhanced proliferation and migration of PA smooth muscle cells (PASMC), is a major cause for elevated PVR in patients with PAH and chronic hypoxia-induced pulmonary hypertension (HPH) (32,54,74). Multiple cellular and molecular mechanisms have been demonstrated to contribute to the development and progression of pulmonary vascular remodeling through enhanced PASMC proliferation and migration, such as signaling cascades involving intracellular free Ca 2ϩ (12,37,50,75), K ϩ channels (51,62,73), Notch (26,69), bone morphogenetic protein/transforming growth factor-␤ (38,42,48), and/or Akt/mammalian target of rapamycin (mTOR) (4,20,23); however, the specific sequence of events involved in the enhanced PASMC proliferation in pulmonary hypertension remains unclear.…”
mentioning
confidence: 99%
“…These investigators found that class I HDAC inhibition or siRNA-mediated knockdown of HDAC1 and HDAC2 blocks PASMC proliferation in association with suppression of AKT phosphorylation and reduction of cyclin D expression. This same group found that sodium butyrate, which selectively inhibits class I HDACs, blocks PDGF-induced PASMC proliferation (Cantoni et al 2013). Work by an independent group demonstrated that apicidin potently blocks proliferation of PASMCs from newborn sheep, further illustrating a key role for class I HDACs in the control of pulmonary vascular cell growth (Yang et al 2013).…”
Section: Targeting Pulmonary Artery Smooth Muscle Cells With Class I mentioning
confidence: 99%
“…Effects of DAPK3 gene knockdown on PDGF-BB-activated intracellular signalling p38 [19], HSP27 [20], Akt [21] and ERK [19] are known as the intracellular signalling molecules involved in SMC proliferation and migration. We, therefore, investigated the effects of DAPK3 gene knockdown on PDGF-BB (10 ng/ml, 20 min)-induced phosphorylation of these molecules.…”
Section: Effects Of Dapk3 Gene Knockdown On Pdgf-bb-induced Lamellipomentioning
confidence: 99%